Medical mystery: Deposition of calcium oxalate and phosphate stones in soft tissues - Capitanini, Alessandro; Xhaferi, Brunilda; Miniello, Vincenzo; Meniconi, Ophelia; Zullo, Claudia; Mannucci, Claudia; Curi, Dritan (Journal of Clinical Nephrology, 2022)
Calcinosis cutis (CC) [1] is an unusual disorder characterized by calcium-phosphate deposition into cutaneous and subcutaneous tissues. There are five subtypes: dystrophic, metastatic, idiopathic, iatrogenic and calciphylaxis. Calciphylaxis or calcifying panniculitis is defined as small vessel calcification mainly affecting blood vessels of the dermis and subcutaneous fat. Despite the predominance of cases in patients with ESRD, calciphylaxis can also be found in patients with normal renal function and normal levels of calcium and phosphate. These cases are often referred to as nonuremic calciphylaxis (NUC), a heterogeneous category with several associations. Literature reveals an association with hyperparathyroidism (28%), malignancy (22%), alcoholic liver disease (17%) and connective tissue diseases (11%) while obesity, liver disease, high-serum calcium (Ca) × phosphorus (P) levels, combined therapies of calcium salts with vitamin D, warfarin and corticosteroids have been observed to increase the likelihood of this disease [2]. The lesions in both nonuremic and uremic calciphylaxis tend to be indistinguishable from each other, initially presenting as tender subcutaneous plaques that progress into nonhealing ulcers with overlying black eschar. Skin changes often begin with a livedo reticularis pattern that can progress to livedo racemes and ultimately retiform purpura. In our clinical case, we describe a patient with multiple risk factors for calciphylaxis, intense widespread calcification (vessels, tendons, joints) and cutaneous calcific stone of calcium and phosphate oxalate not elsewhere described before.